2007
DOI: 10.1177/1087057107304478
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput Screening for Antimicrobial Compounds Using a 96-Well Format Bacterial Motility Absorbance Assay

Abstract: There is a pressing need to develop new antimicrobial drugs because of the increasing resistance of pathogenic bacteria to existing antibiotics. The preliminary development and validation of a novel methodology for the high-throughput screening of antimicrobial compounds and inhibitors of bacterial motility is described. This method uses a bacterial motility swarming agar assay, combined with the use of offset inoculation of the wells in a standard, clear, 96-well plate, to enable rapid screening of compounds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 22 publications
1
16
0
Order By: Relevance
“…Thus, an HTS assay for inhibitors of bacterial motility could be instrumental for the discovery of novel anti-infective drugs. Here we describe the development of an HTS assay for inhibitors of bacterial motility based on a previous method using a soft agar motility assay in 96-well microtiter plates (38). To miniaturize the assay, we first confirmed that in contrast to the case for motile V. cholerae strain C7258, inoculation of the isogenic nonmotile strain C7258 Mot Ϫ in 384-well plates did not interfere with the OD 615 reading even after 24 h of incubation (data not shown).…”
Section: Resultsmentioning
confidence: 69%
See 2 more Smart Citations
“…Thus, an HTS assay for inhibitors of bacterial motility could be instrumental for the discovery of novel anti-infective drugs. Here we describe the development of an HTS assay for inhibitors of bacterial motility based on a previous method using a soft agar motility assay in 96-well microtiter plates (38). To miniaturize the assay, we first confirmed that in contrast to the case for motile V. cholerae strain C7258, inoculation of the isogenic nonmotile strain C7258 Mot Ϫ in 384-well plates did not interfere with the OD 615 reading even after 24 h of incubation (data not shown).…”
Section: Resultsmentioning
confidence: 69%
“…We have developed and validated an HTS assay for smallmolecule inhibitors of bacterial motility based on a previous assay for S. Typhimurium antibacterial compounds that used a 96-well off-center inoculation method (38). The two major shortcomings of the former method were its low throughput and the inability to distinguish between compounds that inhibit motility and those that affect viability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After overnight incubation, bacteria at the initial site of inoculation were collected and reinoculated in the center of another 0.3% agar plate to enrich for nonswarming mutants (45). After three rounds of enrichment, individual bacterial colonies were tested in a 96-well plating assay (46) to identify mutants that failed to swarm in lowpercentage agar. Fig.…”
Section: Methodsmentioning
confidence: 99%
“…As early as 2007, the manual assay that had historically been done in 100 mm dishes or low-density multiwell plates, such as 6-or 24-well plates, and inoculated manually was adapted to the 96-well format and a small library of 960 compounds was run as proof of principle. 23 In 2010, bacteriologists at Southern Research proposed screening up to 200,000 compounds in a motility assay using Vibrio cholera. While it could be done in the 96-well format, the cost and time required could both be reduced if the assay could be further miniaturized to the 384-well format.…”
Section: Bacterial Motilitymentioning
confidence: 99%